Analisis Dinamika Profitabilitas Perbankan yang Terdaftar di Bursa Efek Indonesia (BEI) Tahun 2018-2021 - Elsa Meilinda; Gregorius N. Masdjojo (Ekonomis: Journal of Economics and Business, 2023)
The profitability of banking companies listed on the Indonesia Stock Exchange will not be stable in 2018-2021. Based on previous research studies, there are several different opinions regarding the variables that affect the company's return on assets (ROA). The research or study in this study is a quantitative research model. The population in this study is banking sector companies listed on the Indonesia Stock Exchange for the 2018-2021 period, using a subjective sampling methodology. The amount of data is 156 data obtained from the results of the company's annual financial reports with a sample of 39 companies. The analytical method used is Panel Data Regression Analysis, using the Eviews Test Tool 12. Based on the results of the study, NIM, CAR, NPL have no significant effect on ROA, whereas LDR and BOPO have a significant effect on ROA.